Neural Networks Are Promising Tools for the Prediction of the Viscosity of Unsaturated Polyester Resins - Molina, Julien; Laroche, Aurélie; Richard, Jean-Victor; Schuller, Anne-Sophie; Rolando, Christian (Frontiers in Chemistry, 2019)
Unsaturated polyester resins are widely used for the preparation of composite materials and fulfill the majority of practical requirements for industrial and domestic applications at low cost. These resins consist of a highly viscous polyester oligomer and a reactive diluent, which allows its processability and its crosslinking. The viscosity of the initial polyester and the reactive diluent mixture is critical for practical applications. So far, these viscosities were determined by trial and error which implies a time-consuming succession of manipulations, to achieve the targeted viscosities. In this paper we show that Neural Networks are capable to effectively predict such properties after being trained with a representative set of manipulations. In this work, fifteen unsaturated polyesters have been synthesized through high-temperature polycondensation using usual monomers. Hansen solubility parameters (HSP) were determined from solubility experiment with HSPiP software and glass transition temperatures (Tg) were measured by Differential Scanning Calorimetry (DSC). Quantitative Structure – Property Relationship (QSPR) coupled to multiple linear regressions have been used first to get a prediction of Hansen solubility parameters δd, δp and δh from structural composition. A second QSPR regression has been done on glass transition temperature (prediction vs experimental coefficient of determination R² = 0.93) of these unsaturated polyesters. These unsaturated polyesters were next diluted in several solvents with different natures (ethers, esters, alcohol, aromatics for example) at different concentrations. Viscosities at room temperature of these polyesters in solution were finally measured in order to create a database of 220 entries with 6 descriptors (polyester molecular weight, Tg, polyester-solvent HSP RED, molar volume of the solvent, δh of the solvent, concentration of polyester in solvent). The QSPR method for predicting the viscosity from these 6 descriptors proved to be ineffective (R² = 0.56) given the existence of non-linear phenomena. A Neural Network with an optimized number of 12 hidden neurons has been trained with 179 entries to predict the viscosity. A correlation between experimental and predicted viscosities based on 41 testing instances gave a correlation coefficient R² of 0.90. Thanks to Neural Networks, new developments with eco-friendly reactive diluents can be accelerated.